Oral Method of History in the Investigation into the Resistance - Pušinskytė , Lijana (Genocidas ir rezistencija, 2008)
Oral history is a qualitative method of historic documentation, applied to interview people in order to investigate certain events. Oral history started with an oral tradition, which sociologists began to investigate in the 19th century. It is an oral description of the past events by word of mouth. An oral tradition can encompass an unlimited historic period, while oral history covers only the lifetime of a person. The year 1948 is considered the beginning of the oral method in historiography when modern equipment found its use in historic documentation (the historian A. Nevins started to write down people’s reminiscences).The method of interviewing is an additional documentary testimony, which helps to understand people’s behaviour and motivation. The method is used to compile collections, which embrace various memoirs i.e. historic documents. It gives a chance to people who never wrote memoirs to speak about their past. Oral history examines people’s lives, their experiences, conveying sadness and joys, achievements and failures. The method enables researchers to analyse individual and collective memory. The information obtained during the interview is analysed, and quantitative and qualitative generalisations are made, employing other methods, which are applied to investigate written sources. It is hard to establish the credibility of the facts obtained during interviews, and to reveal the mistakes made by the historian who conducts it. The respondent’s memory presents an even greater problem: he/she can conceal deliberately or unconsciously events or past experiences.Oral history is a particularly valuable source to disclose the history of the resistance and historical memory. It documents the histories of the resistance participants and freedom fighters. On the other hand the method of oral history supplies the researchers with additional facts and information. The interviewing method used in investigating the resistance also presents certain problems, the most important being the following: it is difficult to find witnesses as there are so few of them left; resistance participants give rather subjective evidence; and the facts recorded in oral sources do not correspond with written sources. Oral history supplements written sources, it helps to “hear” the present-day version of the witnesses of that time. Therefore analysis of the interviews of the participants in the resistance and other sources is an excellent chance to reveal what took place in occupied Lithuania.
Keywords: oral history; partisans; literature; poetry